National policies and strategies to reduce informal work in Colombia (2013)
This essay talks about the different definitions that read to informal employment given its origin, as well as its impact on the lives of the citizens also sets out the Regulations Act 789 of 2002, 2010 Act 1429, code noun of the work identified the main features of formal and informal employment as well as the different types of informal employment were evaluated standards and the policies implemented by the Government, type of population which is affected by unemployment, also acknowledged the relationship was identified between unemployment vs. the level of study.